A framework of most effective practices in protecting human assets from predators. Issue 4 (4th July 2019) - Khorozyan, Igor; Waltert, Matthias
ABSTRACT: Widespread damage by large mammalian predators to human assets (e.g., livestock, crops, neighborhood safety) requires the application of non-invasive (i.e., without direct contact with predators) and targeted interventions to promote predator conservation and local livelihoods. We compiled 117 cases from 23 countries describing the effectiveness of 12 interventions designed to protect human assets from 21 predators. We found: (a) the most effective interventions were electric fences, guarding animals, calving control, and physical deterrents (protective collars and shocking devices); (b) the most effectively protected asset was livestock; and (c) the most effective interventions being used were to protect assets from cheetahs ( Acinonyx jubatus ), Eurasian lynx ( Lynx lynx ), gray wolves ( Canis lupus ), and lions ( Panthera leo ). In all of these cases, the relative risk of damage was reduced by 50–100%. We combined these outcomes into a novel framework of most effective practices and discussed its structure, practicality, and future applications.